Development of a micro-heat exchanger with stacked plates using LTCC technology - Vasquez-Alvarez, E.; Degasperi, F. T. [UNESP]; Morita, L. G.; Gongora-Rubio, M. R.; Giudici, R. (Brazilian Soc Chemical Eng, 2010)
A green ceramic tape micro-heat exchanger was developed using Low Temperature Co-fired Ceramics technology (LTCC). The device was designed by using Computational Aided Design software and simulations were made using a Computational Fluid Dynamics package (COMSOL Multiphysics) to evaluate the homogeneity of fluid distribution in the microchannels. Four geometries were proposed and simulated in two and three dimensions to show that geometric details directly affect the distribution of velocity in the micro-heat exchanger channels. The simulation results were quite useful for the design of the microfluidic device. The micro-heat exchanger was then constructed using the LTCC technology and is composed of five thermal exchange plates in cross-flow arrangement and two connecting plates, with all plates stacked to form a device with external dimensions of 26 x 26 x 6 mm(3).
Keywords: CFD; LTCC; Microstructured heat exchanger